Derajat Toksisitas Hemoglobin Pada Penderita Kanker Kolorektal Yang Mendapat Kemoterapi CapeOX - Yusmaidi; Jordy Oktobiannobel; Muhammad Nur; Bella Sabila Dananda (Puslitbang Sinergis Asa Professional, 2020)
Advances in the treatment and use of chemotherapy have been shown to improve the life expectancy rate for colorectal cancer patients. Studies conducted in China and Hongkong have shown that CapeOX combination chemotherapy regimens are more commonly used than in Europe and the United States. However, the use of chemotherapy drugs containing oxaliplatin and capecitabine can cause side effects such as hematological toxicity, which is one of them is anemia. This study aims to determine the difference in the form of a decrease in the average levels of hemoglobin and the degree of hemoglobin toxicity in colorectal cancer patients undergoing CapeOX chemotherapy. The Design in this study is a historical (retrospective) cohort. This study sample was 70 colorectal cancer patients who received CapeOX chemotherapy for 6 cycles at RSUD Dr. H. Abdul Moeloek in 2018-2019. Consecutive sampling is used in the sampling method. The statistical analysis is using Paired T-Test. There is a significant difference in the average hemoglobin level of colorectal cancer patients (p-value = <0.005), which receive CapeOX chemotherapy for 6 cycles. Besides, there is an increase in the number of patients who get hemoglobin toxicity and the chemotherapy cycle. In the first cycle, 59 patients (84.3%) got hemoglobin toxicity after chemotherapy, and the number continued to increase to 69 patients (98.6%) in the sixth cycle. There was a decrease in hemoglobin levels in colorectal cancer patients who received CapeOX chemotherapy with p-value = <0.05 and increased patients who got hemoglobin toxicity.